Performance of Cement Brick by Utilizing Ceramic Tiles Waste - Abd Rahim, Mohammad Kamil; Ismail, Isham (Recent Trends in Civil Engineering and Built Environment, 2025)
Cement brick, a common construction material, contains sand as a core component. As the construction industry’s demand for sand rises annually, concerns about depleting natural resources intensify. In contrast, the potential to repurpose ceramic waste, typically recycled, emerges as a viable strategy for partially substituting fine aggregates and thus could contribute to preserving sand reserves in the construction sector. This study explored the strength characteristics of cement bricks when ceramic waste is used as a partial substitute for sand. Ceramic waste was incorporated at different levels (0%, 10%, 20%, 30%, and 40%) in a 1:3 ratio, yielding 30 brick samples. These samples were subjected to density testing, water absorption testing, and compressive strength testing. The result shows that the sample with 10% achieved the best overall performance in all the tests compared to other ceramic tiles waste incorporated bricks with 26.5 N/mm2 in compressive strength, 7.1% in water absorption and 1938 Kg/m3 in density after curing ages of 28 days. In conclusion, the optimum percentage for the replacement of Ceramic tile waste with sand is 10%.